Asymmetric magnetospheric compressions and expansions in response to impact of inclined interplanetary shock. Issue 12 (25th June 2015) - Samsonov, A. A.; Sergeev, V. A.; Kuznetsova, M. M.; Sibeck, D. G.
Abstract We use global MHD simulations to model the magnetospheric response to an inclined shock that first strikes the duskside magnetosphere. The simulations predict several phenomena related specifically to the inclined shocks. The magnetospheric compression on the duskside exceeds that on the dawnside, and the geocentric distance to the dusk magnetopause varies in a simple step‐like form. The compression on the dawnside is preceded and followed by expansions. For a moderately strong shock, the expansion magnitude reaches several RE behind the terminator plane. The magnetopause and cross‐tail currents in the magnetotail are significantly deformed during and after the shock passage. The position of the magnetotail magnetopause moves by more than 10 RE. This asymmetric magnetopause deformation is mainly related to a strong |Vy| downstream from the inclined shock. The magnetospheric expansion results in a decrease in the horizontal magnetic field at low‐latitude stations, as confirmed by observations.